VISITORS MOTIVES FOR ATTENDING A HYBRID EVENT: A CASE STUDY OF AGRICULTURAL FAIR - Ivkov, Milan; Blešić, Ivana; Popov Raljić, Jovanka; Ivkov Džigurski, Anđelija; Pivac, Tatjana; Jovanović, Tamara (Economics of Agriculture, 2015)
Management of a complex events such as hybrid ones, relies on understanding a modern market trends. The purpose of this study is to determine visitors motives for attending a hybrid event, to identify clusters based on those motives, and to help organizers and exhibitors to meet visitors expectations. Therefore, authors performed ANOVA analysis, factor analysis and hierarchical cluster analysis. The fndings clearly indicate elements of trade fairs and consumer exhibitions integrated in hybrid event and therefore, some of the main motives for visiting those two types of events are also present among hybrid event visitors. However, hybrid event tends to be more than just place for business meetings. It is also a venue for education and leisure time activities. Moreover, event organizers and exhibitors need to pay more attention on their strategic approach to managing their event activities. The paper suggests that hybrid event organizers should focus on establishing dialogue with both exhibitors and visitors.